Peran Ilmu Forensik dalam kasus-kasus Asuransi - Sampurna, Budi (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2008)
Fraud and abuse is not uncommon in the field of insurance. The Coalition AgainstInsurance Fraud reported the cost of fraud in USA, which was significantly high and climbed fromyear to year. Insurance companies, especially both the Life and Health, refer their suspectedfraudulent claims to be investigated. Death verification is generally the objective of mostcontestable or suspicious death claims investigations, however some preliminary investigation findthat a case may have evolved into a criminal matter and further research is necessary. Forensicsciences in these investigations have important role.
Keywords: insurance – forensic